FUNGOS PROMOTORES DE CRESCIMENTO E PRODUÇÃO DE MUDAS DE Pinus taeda L. - Pereira, Fernanda Bortolanza (2017)
Despite the technological advances experienced by the forest sector over the last decades to seedling production, the problems faced twenty years ago, persist today even being the main input for the success of forestry enterprises. In this scope, exploring the richness of microorganisms capable to promoting the growth of plants can be a viable alternative to obtain seedlings with superior morphological and physiological quality, increasing the chances of their survival to the field adversities. A large diversity of microorganisms associated to plants can be used to promote the growth of seedlings or to act to protect them against pathogenic microorganisms. Based on this, the present work was divided into three parts, seeking to obtain at least one fungal isolate with growth promoting properties in Pinus taeda L. seedlings: i) Fungi isolation from field material and evaluation the effect of inoculation on seedling growth, to select at least two isolates with potential for growth promotion; ii) Confirmation of the growth promoting effect of the selected isolates, determining the best time for inoculation; iii) Verification if the selected isolates present, in addition to the growth promoting effect, biological control capacity of Fusarium proliferatum Schltdl. associated with P. taeda seeds. From the mass selection, two isolates were selected, I14R and I51, both belonging to the genus Trichoderma Pers., widely recognized in the literature for the effects of growth promotion and biological control. In the biological control experiment of F. proliferatum, both isolates were efficient in the direct in vitro comparison test. However, in the in vivo assay, none of the isolates proved to be efficient due to the way of inoculation thereof.